Dynamic Analysis of Commodity Prices Influence on Broiler Chicken Prices in Malaysia - Che Rose, Farid Zamani; Sapar, Marni (Journal of Social Transformation and Regional Development, 2024)
The poultry industry in Malaysia has been successful to produce more than the domestic demand over the years. Recent hike of animal feeds prices globally is an important issue in developing countries such as Malaysia that affects the cost of broilers production. This study aims to investigate the factors affecting the cost of broilers production in Malaysia as well as to evaluate the performance of structural time series model in forecasting the ex-farm broiler price. The factors that are included in this study are the imported ingredient for animal feeds, exchange rate and crude oil prices. This research revealed the strength of relationship between ex-farm broiler and macroeconomic variables prices that contributed to costs production of broiler in Malaysia. The structural time series model applied in this study shows that the ex-farm broiler price can be represented by a basic structural time series model. Hence, the findings from this study suggests a different approach to policy makers to ensure a low dependency on foreign resources and to protect the poultry industry in Malaysia.